Fungi with high ability to crunch multiple Polycyclic Aromatic Hydrocarbons (PAHs) from the pelagic sediments of Gulfs of Gujarat. (June 2021) - Mahajan, Mayur; Manek, Devika; Vora, Nishant; Kothari, Ramesh K.; Mootapally, Chandrashekar; Nathani, Neelam M.
Abstract: Marine ecosystem harbors diverse microbial diversity adapted to varied environmental conditions and stress. Gujarat possesses a wide coastline with unique and diverse niche in its two Gulfs. PAHs enter marine environments through various anthropogenic discharges and act as a threat to environment due to their xenobiotic nature. In the present study, sediment cores were collected across 4 coordinates, each from Gulf of Kutch and Khambhat; while one from Arabian sea. These samples were enriched for fungal growth in basal medium supplemented with naphthalene, pyrene, phenanthrene, anthracene and fluoranthene. Eight isolates were obtained from 3 samples and checked for tolerance against 5 PAHs followed by assessment of their biodegradation ability. Penicillium ilerdanum NPDF1239-K3-F21 and Aspergillus versicolor NPDF190-C1-26 showed >75% ability to degrade multiple PAHs. The results reveal the potential of fungal isolates from pelagic sediment for further in situ optimization and application in PAH removal from contaminated soil and sediment. Highlights: On-shore activities influence the function of deep sediment microbiota. Pelagic sediment, Gujarat Gulf hosts potent fungus for bioremediation. Penicillium ilerdanum and Aspergillus versicolor showed high PAH degradation.